REGULARITIES OF SOCIAL-CULTURAL AND PSYCHOLOGICAL ADAPTATION OF STUDENTS FROM DIFFERENT COUNTRIES (ON THE EXAMPLE OF ROMANIA AND ARMENIA) - Ghazaryan , G. H.; Babayan , L. A.; Aristakesyan , D. A. (Modern Psychology, 2019)
This article discusses the features and patterns of socio-cultural and psychological adaptation of freshmen to study at University, especially students who receive higher education outside their country. In this regard, three groups of YSMU freshmen were examined in Armenian, Russian and English-speaking students, as well as in the Romanian University "Dunarea de Jos" a study was conducted by students speaking Armenian, Romanian, Albanian and Arabic. To achieve this goal, first-year students of two universities were investigated - three groups of students of Yerevan State Medical University named after M. Heratsi (Armenian-speaking, Russian-speaking and Englishspeaking) and students of the medical center in Dunarea de Jos, Galati city, Romania (groups of students from Armenians, Romanians, Albanians and Arabs). Based on many years of research, we have concluded that the process of adaptation of first-year students studying in different countries is largely due to the relationship between the student and the teacher, fellow students and socio-cultural conditions of the country. The main principles of effective relations between students and teachers, as well as fellow students, are communication, dialogue, active perception, self-disclosure, the formation of value-oriented orientation, the development of responsibility.
Keywords: adaptation, sociocultural features, interpersonal communication, tertiary education institutions